CRESCIMENTO, DESENVOLVIMENTO E PRODUTIVIDADE DE SOJA EM DIFERENTES ÉPOCAS E DENSIDADES DE SEMEADURA - Umburanas, Renan Caldas (2014)
This study evaluated the growth and yield of soybean plants cultivar BMX Energia® sown at three sowing times (the middle of October, November and December), four seeding rates (150, 250, 350 and 450 thousand plants ha?¹), and two seasons (2012/13 and 2013/14), in the center-south of Parana State. The experimental design was a randomized complete block design with three replications in a split-plot arrangement, with sowing dates arranged as main plots and seeding rates as subplots. During crop growth, plants were sampled at growth stages V6, V9, R3 and R5, and plant growth and light interception were analyzed. At harvest (stage R8) yield components and crop yield were evaluated. The plants sowed in of December had lower plant height, leaf area index (LAI), photosynthetically active radiation absorption and growth period than plants sowed earlier, and had lower production of flowers, especially at lower seeding rates. The plant height and LAI increased linearly with increasing seeding rate. Plant height and LAI showed high correlation with relative grain yield. Plants sowed in december (late) had lower yield in two seasons, and in the season 2012/13 the hundred grain mass had greater relationship with yield while in the 2013/14 season the number of grains per area had higher relationship. The increase of seeding rate increased yield linearly in two seasons, and its effect was on components number of grains per area and pods per plant. There was interaction in yield between sowing times and seeding rates in 2012/13 season. The plants sowed in October did not differ among the seeding rates, the plants sowed in November at seeding rate of 350 thousand plants ha?¹ were more productive that the seeding rate of 150 thousand plants ha?¹, and in the plants sowed in December the increase of seeding rate increased yield. Higher seeding rates in December (late) can provide higher income to the growers when the market price is favorable.